2022
DOI: 10.46338/ijetae0822_01
|View full text |Cite
|
Sign up to set email alerts
|

The Metaverse to Enhance Safety Campaign toward Shipping Industry (Case Study: The Development and Implementation of Metaverse in Government-Owned Corporation)

Abstract: The Metaverse concept that uses Virtual Reality technology is a highly developed technology. We present an application from the metaverse concept using the Oculus Rift for a safety campaign with a safety training approach. This paper describes comprehensively the concept, design, development, and evaluation of the implementation of the metaverse towards the Government-Owned Corporation. The results of the evaluation involving 60 respondents prove that safety training has gotten very good results. The test also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The results indicated positive outcomes for all these factors. The study also found that participants aged between 35 and 55 years were able to overcome errors while using the metaverse (Fajar et al , 2022).…”
Section: Findings: Metaverse Cases In Trainingmentioning
confidence: 91%
See 3 more Smart Citations
“…The results indicated positive outcomes for all these factors. The study also found that participants aged between 35 and 55 years were able to overcome errors while using the metaverse (Fajar et al , 2022).…”
Section: Findings: Metaverse Cases In Trainingmentioning
confidence: 91%
“…Discussion: lessons from the cases A review of case studies demonstrated that the metaverse can be applied in a wide range of training domains, including safety (Fajar et al, 2022), disaster response (Hsu et al, 2013), maintenance (Siyaev and Jo, 2021), health care (Chen et al, 2022) and military (Optimus system, 2019). The metaverse provides a realistic training simulation that can mitigate the risks associated with onsite training.…”
Section: Using the Metaverse In Trainingmentioning
confidence: 99%
See 2 more Smart Citations